2015
DOI: 10.1007/s00436-015-4341-2
|View full text |Cite
|
Sign up to set email alerts
|

Transmission electron microscopic observations on ultrastructural alterations in Schistosoma mansoni adult worms recovered from C57BL/6 mice treated with radiation-attenuated vaccine and/or praziquantel in addition to passive immunization with normal and vaccinated rabbit sera against infection

Abstract: Although the current treatment of schistosomiasis relies largely on praziquantel (PZQ), it has not been successful in significantly reducing the overall rate of disease cases, one of the suggested reasons being the inevitable resistance to PZQ. Previous studies showed that radiation-attenuated vaccine provides protection against Schistosoma mansoni in a host of various species. In the present study, we evaluated the effect of various vaccination strategies in C57BL/6 mice, including single or multiple vaccinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 64 publications
1
17
0
Order By: Relevance
“…Additionally, the ultrastructural changes in adult male worms included degeneration of the tegument and subtegumental layers as well as shrinkage of the muscle with embedded spines. These findings were in accordance with those of El-Shabasy et al (2015) who confirmed the same ultrastructural transformation of the tegument induced by PZQ.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Additionally, the ultrastructural changes in adult male worms included degeneration of the tegument and subtegumental layers as well as shrinkage of the muscle with embedded spines. These findings were in accordance with those of El-Shabasy et al (2015) who confirmed the same ultrastructural transformation of the tegument induced by PZQ.…”
Section: Discussionsupporting
confidence: 92%
“…Both scanning and transmission electron microscope play an important role in elucidating the detailed morphology and different alterations of the S. mansoni tegument allowing the interpretation of its functionality (Senft & Gibler 1977, El-Shabasy et al 2015). These methods have been employed by several researchers (de Oliveira et al 2012, El-Shabasy et al 2015) and help to explain the mechanisms of action of anti-schistosomal drugs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The detection and identification of these helminths are done by morphological characterization. Moreover, a complete understanding of micro-morphological features plays an important role in the development of vaccines (Degheidy and Shalaby, 2010) and alterations in the ultrastructure of schistosome worms are useful for evaluation of anti-schistosomal drugs (El-Shabasy et al, 2015) for which there is a necessity of understanding normal ultrastructural morphology. Scanning Electron microscopy (SEM) allows better characterization of taxonomically significant structures and is important for generating a more precise species identification and the confirmation, description and/or redescription of species of nematodes (Rebello et al, 2012).…”
Section: Introductionmentioning
confidence: 99%